Organisational culture as a barrier to women's promotion - O'Connor, Pat (Economic & Social Studies, 1996)
Over the past five years increasing attention has been paid to the importance of what Witz and Savage (1992) have described as the gendered nature of organisations. This paper focuses on what they have called the "significance of difference" within the context of a discussion of the perceived reality of organisational culture. Using a thematic qualitative analysis of data from 40 focus groups, involving a stratified random sample of 162 women at middle and senior levels of the Administrative, Nursing and Paramedic sectors of two Irish Health Boards, four aspects of this organisational culture are described viz., the perceived reality and implications of a male hierarchical model of authority, the perceived reality of a woman's place in that structure; the perceived marginalisation of female professional projects and the existence of a coping style of Management. The paper suggests that these aspects of organisational culture are by no means peculiar to these Health Boards. Indeed, these Boards are unusual only in so far as they have legitimated a challenge to male hegemonic culture by implicitly valuing "difference", through prioritising the idea that women ? who constitute the majority of their staff ? should be employed "at the top of their capacity" (Doherty, 1994).
Keywords: Organisation culture; Female employment; Ireland; Health workers